Effect of inorganic and organic zinc supplementation on semen quality in Murrah buffalo (Bubalus bubalis) bulls - IMAM, S; ANSARI, M R; Kumar, RIPU SUDAN; MUDGAL, VISHAL; VARSHEN, V P; DAS, R S (The Indian Journal of Animal Reproduction, 2023)
The present study-was conducted to elucidate the effect of inorganic (zinc sulphate) and organic (zinc propionate)’ zinc supplementation on in vitro semen fertility and semen quality in buffalo bulls. Twelve buffalo bulls of about 2 years of age and 302.0± 1.6 kg average body weight were divided into 3 equal groups. All the animals were fed on wheat straw and concentrate mixture to meet their nutrient requirement;I _ Animals in-group I were treate·d as control, whereas animals in group II and III were experimental and were supplemented ·with 70 ppm and 3 5 ppm zinc through zinc sulphate and zinc propionate, respectivel1i1 · This feeding practice lasted for 6 months. Bulls were trained to donate semen into artificial vagina. After 3 months of experimental feeding, 6 ejaculates from each bull were collected to study the effect of zinc supplementation (?D sperm fertility and semen characteristics. Statistical analysis of the data revealed that thete was no effect of zinc supplementation on semen pH and semen volume; however, sperm concentration. mass motility and individual motility differed significantly (P<9.o 1) among the groups and were higher in zinc-supplemented groups as .compared to control. Similarly, reaction time (second), live sperm(%) and acrosomal integrity (%) were significantly (P<0.05) different in 3 groups. In vitro fertilizing ability test HOSST ·(%) and_ BCMPT (distance in mm) revealed significantly (P<0.05) higher fertilizing ability of sperm in zinc-supplemented groups as compared to control group. Results further revealed that live sperm (%), actosomal integrity °lo)_ and in vitro fertilizing ability of sperm (HOSST, %) and BCMPT (distance in mm) were significantly (P<0.05)higher in zinc propionate supplemented group as compared to zinc sulphate uppiemented group. It may be concluded thatsupplementation of zinc as zinc propionate improved semen · quality as well as in-vitro sperm· fertilizing ability as compared to zinc sulphate.